2021
DOI: 10.26605/medvet-v15n4-2266
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrients and essential amino acids on digestive process of the freshwater teleost Matrinxã

Abstract: The objective of this work was to evaluate the effect of macronutrients and essential amino acids on digestive process of the freshwater teleost Matrinxã (Brycon amazonicus). Juveniles were fed with diets containing starch plus free amino acids or oil plus free amino acids for 15 days. These fish were compared with others fed with diets containing starch or oil without addition of free amino acids. After the experimental span, 12 fish from each treatment were randomly sampled to collect stomach, pyloric cecum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The best growth rates were observed in fish fed the BH + DD diet, this result was also reported by (Wen et al 2018), who combined a wet diet with and hearts (1: 1) and found them to be good growth promoters for S. aequifasciatus. The presence of free amino acids in the diet stimulates feeding chemoreceptors (Santos et al 2021, Camilo et al 2021. In a study with larvae of Piaractus mesopotamicus it was observed that the use of water from the hatching of brine shrimp stimulated the behavior of capturing food, these results being attributed to the presence of dissolved substances (Tesser e Portella 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The best growth rates were observed in fish fed the BH + DD diet, this result was also reported by (Wen et al 2018), who combined a wet diet with and hearts (1: 1) and found them to be good growth promoters for S. aequifasciatus. The presence of free amino acids in the diet stimulates feeding chemoreceptors (Santos et al 2021, Camilo et al 2021. In a study with larvae of Piaractus mesopotamicus it was observed that the use of water from the hatching of brine shrimp stimulated the behavior of capturing food, these results being attributed to the presence of dissolved substances (Tesser e Portella 2006).…”
Section: Discussionmentioning
confidence: 99%